Luther A Life - Todd, John M. (New York Crossroad Pub Co, 1982)
Biography of Martin Luther, a preacher and theologian of the 16th century.
Keywords: Luther, Martin, -- 1483-1546. Reformation -- Biography. Réforme (Christianisme) -- Biographies